Features of organ-saving foot amputation associated with ozone therapy, local application of autologous platelet-rich plasma and vacuum sanitization of postoperative wound in patients with ischemic-gangrenous form of diabetic foot syndrome - V. D. Fundiur; V. K. Grodetskyi; S. O. Yakobchuk; O. Y. Khomko; I. M. Kozlovska; Yu. V. Fundiur; O. V. Fundiur (Kazimierz Wielki University, 2021)
Improvement of reparative process of the chronic wounds with the insufficiency of peripheral blood suppling in patients suffering from diabetes mellitus is an important issue requiring further investigation. An optimal choice of surgery, effective renewal of blood supply and active stimulation of tissue repair on the cellular level are essential components of success treatment of this problem. Objective of research: From 2017 to 2020, the efficiency of one of the variants of organ-saving surgery performed on 210 patients with an ischemic-gangrenous form of diabetic foot syndrome was studied. Materials and methods. Control group included 104 patients (49.52%), were the treatment carried out in accordance with the standard scheme. The main group (106 patients - 50.47%) in addition to the standard therapy have used regional ozone therapy, vacuum sanitization and local application of autologous platelet-rich plasma (APRP). Results. These proposed measures reduced the period of clinical treatment to 24±1,2 days in the main group compared to 37±2,4 in the control one. 2 years later, patients of the main group confirmed the formation of a foot stump functionally adapted for walking with angular dislocation of fragments of the cuboid and scaphoid bones. Two years after foot amputation due to the ischemic-gangrenous form of diabetic foot syndrome (DFS), the amount of repeated above knee amputations was 1.8 times higher in the control group in comparison with the main group, which is indicative of a reasonable use of the complex of activate a reparative process in the wound. Conclusions: The suggested modification of the organ-saving and partial foot amputation in patients with IV degree of ischemia and DFS is indicative of a possibility to perform such kind of surgery as a variant of choice. The complex of proposed additional measures including regional ozone therapy, vacuum sanitization and local administration of autologous platelet-rich plasma activates a reparative process of a chronic foot wound and promotes an effective treatment of patients with ischemic-gangrenous form of DFS.